2020
DOI: 10.1186/s12882-020-01810-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between reduced kidney function and hearing loss: a cross-sectional study

Abstract: Background: The relationship between kidney function and hearing loss has long been recognized, but evidence of this association mostly comes from small observational studies or other populations. The aim of this study is to explore the association between reduced kidney function and hearing loss in a large population-based study among the middle-aged and elderly Chinese. Methods: Data collected from the Chinese Health and Retirement Longitudinal Study (CHARLS) in 2015 were used for analysis. A cross-sectional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
2
18
4
Order By: Relevance
“…This prevalence is somewhat lower than in previous reports, 29%–40%, 10 12 but much higher than that in the general population of over 5%. 5 In our study, the overall prevalence of SNHL was 12.1%, which was higher than the 1.2% reported in the Korean adolescents 27 (no data available for CHL). Therefore, we suggest that the possibility of HL should be considered in pediatric CKD patients, requiring surveillance and early intervention, if necessary.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This prevalence is somewhat lower than in previous reports, 29%–40%, 10 12 but much higher than that in the general population of over 5%. 5 In our study, the overall prevalence of SNHL was 12.1%, which was higher than the 1.2% reported in the Korean adolescents 27 (no data available for CHL). Therefore, we suggest that the possibility of HL should be considered in pediatric CKD patients, requiring surveillance and early intervention, if necessary.…”
Section: Discussioncontrasting
confidence: 71%
“…HL is more prevalent in patients with chronic kidney disease (CKD) than in the general population. 5 8 While the overall prevalence of HL with CKD is 40%–75% in adults and about 40% in children, 9 10 SNHL is more common than CHL in this population, 8 11 with the prevalence of SNHL in adult patients estimated to be 20%–87% and 29%–40% in children. 10 12 Several potential hypotheses have been proposed to explain the higher prevalence of HL in patients with CKD; one of them is that the kidney and the stria vascularis of the cochlea share physiologic, ultrastructural, and antigenic characteristics that could underlie the link between CKD and HL.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Participants with CKD Stages 3b-5 had less social participation ( 23 ). Reduced kidney function was also independently associated with hearing loss, which may cause social isolation ( 24 ). The previous studies both revealed that CKD was associated with social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study in adults confirmed that reduced kidney function is independently associated with hearing loss development. 71 However, aminoglycosides and glycopeptides are also known to be nephrotoxic, 72 , 73 possibly leading to reduced kidney function. The exact mechanisms that may influence systemic and cochlear electrolyte homeostasis in children are still unexplored and unclear, which urges the need for further in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%